Analysis of Exhumations Carried Out in Three Divisions of Sindh - Muhammad Wasif Saleem, Dolat Singh, Taqia Fauzia, Azhar Rashid, Shazia Hashmat, Shomaila Ameer Alam (Pakistan Journal of Medical & Health Sciences, 2023)
Aim: To determine the causes of death on exhumation in three divisions of Sindh, Pakistan Study Design: Cross-sectional Place and Duration of Study: Department of Pathology, Chandka Medical College, Larkana Methods: 131 exhumations carried over 1 year were included in the study. In accordance with protocol, the graves were first identified and body was removed from it. Routine autopsy was carried out. Written consent for obtaining data was taken from the relatives present and a standard proforma was used to note findings. Samples for histopathology were also taken and cause of death was evaluated. After taking relevant information, the bodies were buried in accordance with the religious and cultural norms of the relatives. Data was entered and analyzed using SPSS 22.0. Results: Males were more commonly exhumed. 21-40 years age group was most commonly involved. Most exhumations were carried out in Larkana. Most common weapon used was forced blunt trauma. Almost all bodies were at different stages of decomposition. We then observed the type of weapon/medium used. All 131 cases were of unnatural death. We observed that the most common weapon used was a hard blunt object (n=41; 31.29%), water causing drowning (n=34; 25.95%), sharp forced trauma (n=21; 16.03%) and strangulation (n=19:14.50%) were commonly used. Whereas, the least commonly used were firearms (n=16; 12.21%). According to our observation, 57.25% (n=75) were partially decomposed, 40.45% (n=53) had advanced decomposition whereas 2.29% (n=3) had no decomposition at all. Practical Implication: Analysis of exhumations is crucial for uncovering forensic evidence, resolving criminal cases, and providing closure to families. It helps ascertain causes of death, identify potential foul play, and contribute to the justice system’s integrity. Additionally, exhumation analysis aids in refining investigative techniques and advancing forensic science. Conclusion: We recommend exhumation when required be carried out in females as well. We also recommend early exhumation in cases of suspected foul-play. Our data may help in future planning of policies regarding exhumation. Keywords: Exhumation; 3 Divisions of Sindh; Decomposition, Causes of Death, Drowning, Firearm Injuries, Weapon